Human-machine collaboration and emotional intelligence in industry 5.0 - Agarwal, Priyanka; Jain, Vishal; Kumar, Nitendra 1989-; Pal, Surya Kant; Rosak-Szyrocka, Joanna (IGI Global, 2024)
In the rapidly evolving landscape of Industry 5.0, integrating emotional intelligence into the industrial framework is becoming increasingly crucial. Organizations are trying to navigate this uncharted territory and seeking guidance on understanding, implementing, and ethically managing artificial emotional intelligence (AEI). However, the absence of a comprehensive resource addressing these complexities has left a significant void in academic scholarship and industrial practice. Human-Machine Collaboration and Emotional Intelligence in Industry 5.0 offers a holistic exploration of emotion recognition, affective computing, and human-robot interaction. It equips readers with the knowledge and tools to successfully integrate AEI into Industry 5.0, ensuring a harmonious collaboration between humans and machines. This book is a go-to resource for scholars, industry professionals, and decision-makers seeking to leverage emotional intelligence in the Fifth Industrial Revolution by addressing practical implementations, ethical considerations, and real-world impacts